Successful mediastinal teratoma resection in a child by assisted VATS: a case report - Masato Kojima; Ryo Touge; Sho Kurihara; Isamu Saeki; Shinya Takahashi (Journal of Cardiothoracic Surgery, 2024)
Abstract Background Video-assisted thoracic surgery (VATS) is widely used for thoracic lesions in pediatric patients. VATS is also applied to pediatric mediastinal tumors if there is no adhesion or invasion between the tumor and adjacent neuronal and cardiovascular structures. Here, we present a pediatric case of mediastinal teratoma in which the tumor adhered to the superior vena cava, and resection was safely completed using assisted VATS, an integrated surgical approach comprising mini-thoracotomy with video assistance. Case presentation A 9 year-old girl presented with right shoulder pain. Chest radiography and computed tomography revealed a 5.4 × 5.1 × 5.8 cm mass in the right upper anterior mediastinum. She was presumed with a mature teratoma, and resection was performed by assisted VATS with muscle sparing axillar skin crease incision (MSASCI) for a mini-thoracotomy. The procedure was safely completed, with the patient discharged on postoperative day 5. At 1 year postoperatively, there was no recurrence with excellent motor and cosmetic results. Conclusions The combination of MSASCI and VATS would be useful not only for mediastinal teratomas but also for other mediastinal tumors and almost all other thoracic lesions in pediatric patients.